The Relationship between Organizational Commitment and Intention to Quit: The Malaysian Companies Perspectives - Kuean, W.L.; Kaur, S.; Wong, E.S.K. (Asian Network for Scientific Information (ANSINET), 2010)
This study examines the relationship between organizational commitment and an employee’s intention to leave the organization in a Malaysian situation and includes the moderating effects of decision-making participation and the employee’s work-effort on the employee-employer relationship, as well as on their job work-effort. This study has two objectives, firstly to determine the relationship between organizational commitment and intentions to leave among working adults in Malaysia. Secondly, is to investigate the moderating effect of decision-making participation and the effort needed to express an intention to leave by these same adults. This is a descriptive study based on a 300-sample size survey conducted among working adults in Malaysia. There were 189 responses received, representing a response rate of 63%. Of these, only 181 responses with no missing values were used for data analysis as the others were rejected as being incomplete. The correlation analysis results from this study confirmed previous researcher’s observations linking higher organizational commitment with lower intentions to leave the organization. The results suggest that among the three components of organizational commitment, the employee’s affective or affection commitment to the organization was the most important predictor of intentions to leave. Employees were less likely to leave when they have an emotional commitment to and identify with, their organization. Cultivating an organizational culture of shared values and involving employees in the goal setting processes would further enhance employee’s acceptance of and alignment with, stated organizational goals. This promotes greater personal organizational commitment and eventually reduces employee’s intentions to leave the organization.